2014
DOI: 10.1111/appy.12131
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted therapy for improving social interactions and activity participation among institutionalized older adults: A pilot study

Abstract: By interacting with a robot pet, such as Paro, the communication, interaction skills, and activity participation of the older adults can be improved. The robot-assisted therapy can be provided as a routine activity program and has the potential to improve social health of older adults in residential care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 19 publications
4
79
0
5
Order By: Relevance
“…Paro, a seal-like robot and other zoomorphic robots have built on the success of animal therapy and been successfully used to facilitate therapeutic work with PWD, to enhance social interactions and reduce social isolation [5,6,7,8,9]. Robotic animals can be more acceptable than real animals for reasons of safety, hygiene, and being hypoallergenic.…”
Section: Use Of Social Robots For Pwdmentioning
confidence: 99%
“…Paro, a seal-like robot and other zoomorphic robots have built on the success of animal therapy and been successfully used to facilitate therapeutic work with PWD, to enhance social interactions and reduce social isolation [5,6,7,8,9]. Robotic animals can be more acceptable than real animals for reasons of safety, hygiene, and being hypoallergenic.…”
Section: Use Of Social Robots For Pwdmentioning
confidence: 99%
“…Even if the results vary and stem from pilot studies (for a current study with a relatively large sample size see ref. 10), this research demonstrates overall positive effects of pet robots on the older residents, sometimes suffering from dementia, especially in comparison with control groups without living animals 4 6 9 11–13. Above all, where the use of animals seems problematic, or where this appears too costly, pet robots stand out as a notable alternative.…”
Section: State Of Research and Target Of Inquirymentioning
confidence: 65%
“…Further, pet owners can be injured by the scratching and biting of potentially stressed animals. The death of a beloved pet will lead to mourning and in some cases this will relativise the psychological benefits they provided, at least if this happens with some frequency 3 4 16 18…”
Section: Benefits Of and Concerns About Live Animals In Domestic Settmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the beneficial effects of other pets including exotics (e.g., snakes and lizards) and even robotic animals (e.g., robotic seals) [63,64]. A single-group pretest and posttest design [63] found that participants in a residential care facility had better communication and social skills and more activity participation after interacting with Paro, a robotic seal [63], whereas a better-controlled randomized controlled trial found significant decreases in loneliness with Paro [64]. Not all individuals may be good candidates for dog or cat ownership due to health or financial circumstances.…”
Section: Resultsmentioning
confidence: 99%